IMPLEMENTASI PROGRAM PENANGANAN KORBAN KEKERASAN SEKSUAL PADA ANAK LAKI-LAKI DI KABUPATEN KARAWANG TAHUN 2017-2019 - Setyani, Nindi Nurfahmi; Rifai, Maulana; Marsingga, Prilla (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2021)
The level of sexual violence against children is increasing every year, both for girls and for boys. Victims who have experienced sexual violence certainly need serious handling so that other problems do not occur in the future. One of the functions of the government is to provide services to the community and to empower people to participate in government administration. One form of service is by providing an Integrated Service Center for the Empowerment of Women and Children (P2TP2A) in each region. The Integrated Service Center for the Empowerment of Women and Children (P2TP2A) has the task of preventing, completing and recovering victims of acts of violence. Therefore, the purpose of this study was to determine whether the implementation of the P2TP2A handling program in Karawang Regency has been running optimally or not. This study uses a descriptive method with a qualitative approach. The data collection techniques used in this study were interviews, observation, documentation, and triangulation. The result of this research is that the handling of boys sexual violence victims has not run optimally, this is due to the lack of information delivery and socialization to the public regarding the existence of this program. In addition, the response from the community regarding the need for handling victims of sexual violence against boys in Karawang Regency is still low. Keywords: Implementation, Integrated Service Center for Women and Children Empowerment, Handling Victims of Sexual Violence in Boys, Karawang Regency.